2013
DOI: 10.1136/annrheumdis-2013-203371
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Fms-like tyrosine kinase 3 ligand (Flt3L) signalling protects against collagen-induced arthritis

Abstract: ObjectiveComprehending the mechanisms that regulate activation of autoreactive T cells and B cell antibody production is fundamental for understanding the breakdown in self-tolerance and development of autoimmunity. Here we studied the role of Fms-like tyrosine kinase 3 ligand (Flt3L) signalling in the pathogenesis of collagen-induced arthritis (CIA).MethodsCIA was induced in mice lacking Flt3L (Flt3L−/−) and wild-type (WT) littermates (C57/BL6, 8–10 weeks old). Mice were killed in the initial phase (acute pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…These findings contradict previous data, showing that Flt3L KO mice are protected from developing arthritis [5]. What could be the explanation for these conflicting results?…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…These findings contradict previous data, showing that Flt3L KO mice are protected from developing arthritis [5]. What could be the explanation for these conflicting results?…”
contrasting
confidence: 91%
“…Ramos et al [3] also demonstrated that peripheral blood monocytes not only appear to be the primary source of Flt3L in RA patients but also express the highest levels of the Flt3L receptor (Flt3/CD135), suggesting an autocrine regulation. Flt3L KO mice are protected from developing arthritis in a CIA model and have lower levels of proinflammatory cytokines, CII-specific IgG2a antibodies, and decreased synovial inflammation [5].…”
mentioning
confidence: 96%
“…Induction of CIA : In the first CIA model, 100 μL chick type II collagen dissolved in 0.01 m acetic acid to a concentration of 4 mg mL −1 was emulsified in an equal volume of Freund's complete adjuvant and administered intradermally at the base of the tail of C57BL/6N mice (15 mice per group). On day 21, a booster emulsion prepared with type II collagen and Freund's incomplete adjuvant was administered intradermally near the primary injection site . The truncated IL‐17RC peptide (150 μg, 100 μL) was injected intraperitoneally three times per week on day 14 after the initial immunization whereas PBS was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The hind‐paw was scored every day and the swelling was measured every 3 d. On day 37 after the first immunization, mice were anesthetized. The clinical scores were assigned as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, local knee exposure to Flt3L aggravates arthritis in mice [30]. Furthermore, Flt3L-deficient mice are protected against collagen-induced arthritis, and blockade of Flt3 signaling reduces the severity of antigen-induced arthritis in mice [34,35].…”
Section: Introductionmentioning
confidence: 99%